Analysis the Influence of Integration PKM-P, PKM-KC and PKM-T in Subjects Writing Techniques and Presentation on the Execution Time of the Final Project in Mechanical Engineering Diponegoro University - Norman Iskandar; Rifky Ismail; Friady Gumilar (International Journal of Engineering Education, 2019)
This research is motivated by the study period of Mechanical Engineering students in UNDIP that is still quite long, more specifically dealing with the execution time of the Final Project (FP) that still quite long compared to the average in other departments in the Faculty of Engineering of Diponegoro University. Students can take the FP if it has to pass at least 115 credits from total of 144 credits, and with a GPA above 2.25. Final project is a compulsory subject in 7th semester, but most of the students can pick them up in 8th to 10th semester. The final task takes time because nearly three months is required to be able to get a topic and a supervisor, the details of which one month process of signing up to the FP coordinator and the distribution of students into groups of KBK (there are four  KBK), one month distribution process in the KBK to determine the FP lecturers and one month for the initial interaction with the FP lecturers. Problems in the FP including the theme / topic of the final project, the cost and process of making proposals, and the final report. The objectives of this research is to build synergies between the Writing Techniques and Presentation subject in the 6th semester with the FP subject in the 8th semester by using the momentum of  PKM in the 7th semester. This study also aims to improve the quality of the final project, such as issues related time on KBK election, election supervisor FP, FP election topics, funding for FP workmanship as well as shortening the time to write a proposal and the final report. It is expected to shorten the FP program and the study period. This research is a class act. The planned action is integrating PKM in lectures Writing and Presentation Techniques in 6th semester. The planned action is integrating PKM in Writing Techniques and Presentation lectures in 6th semester. The planned action is integrating PKM in Writing Techniques and Presentation lectures in 6th semester. So that the output of the lectures  of writing and presentation technique is to make a FP proposal to level ready for seminar and convert FP proposal into PKM until ready submitted to DIKTI. Subjects were students of S1 Mechanical Engineering UNDIP in the 6th semester. The research objects is Writing techniques and Presentation lectures. Stages of research include: preparation, planning, action, reflection. From the results of the study with a sample of students as many as 33 people showed for the evaluation of short-term target success rate of 80% PKM proposal ready to submit and FP proposals  ready for a seminar, the achievements obtained was 100% of students have successfully made a proposal FP and PKM with the guidance of lecturer KBK selected. From all proposals PKM and FP that have been made, as many as 10 titles PKM proposal meets the standards to be sent to the DIKTI  and as many as 17 titles FP proposal is a direct recommendation from lecturers.